Savagely Sentimental: The Creation and Destruction of the Sentimental Indian in Lydia Maria Child’s Hobomok - Robyn Johnson (eTropic: electronic journal of studies in the tropics, 2017)
Lydia Maria Child, known during her time for controversial writing, has largely fallen out of focus in current feminist studies. As an activist, many of her pieces questioned the role of gender, race, and sexuality in the early nineteenth century. Hobomok, published in 1824, is considered one of her most radical tales. Detailing the marriage and procreation of a white woman and a Native American man, Hobomok shocked audiences with its content. Many critics have come to view Hobomok as a piece of feminine rebellion, seeing Mary Conant as an example of feminine refusal. Although such interpretations hold merit, they often ignore the role of Hobomok, the titular character. Hobomok is the first visible experimentation of the sentimental male. Other adaptations of the sentimental male do not appear in literature until Harriet Beech Stowe’s Uncle Tom’s Cabin. I argue that Child attempts to create one of the first sentimental males through Hobomok by compounding the qualities of masculinity and femininity of the era. Child is able to attempt such a task due to the pre-established concept of the “Noble Savage,” which already imbued Indians with sentimental attributes, and provides a valid and even rational justification for his extinction. Once establishing Hobomok as a “Noble Savage” and compounding masculine and feminine qualities within him, Child can easily and completely dismiss him so as to minimize his threat to white nineteenth century society. It is the compilation of his “noble savagery” and his feminine qualities that engenders his extermination.